Earthworms as candidates for remediation of potentially toxic elements contaminated soils and mitigating the environmental and human health risks: A review - Ran Xiao; Amjad Ali; Yaqiong Xu; Hamada Abdelrahman; Ronghua Li; Yanbing Lin; Nanthi Bolan; Sabry M. Shaheen; Jörg Rinklebe; Zengqiang Zhang (Environment International, 2022)
Global concerns towards potentially toxic elements (PTEs) are steadily increasing due to the significant threats that PTEs pose to human health and environmental quality. This calls for immediate, effective and efficient remediation solutions. Earthworms, the 'ecosystem engineers', can modify and improve soil health and enhance plant productivity. Recently, considerable attention has been paid to the potential of earthworms, alone or combined with other soil organisms and/or soil amendments, to remediate PTEs contaminated soils. However, the use of earthworms in the remediation of PTEs contaminated soil (i.e., vermiremediation) has not been thoroughly reviewed to date. Therefore, this review discusses and provides comprehensive insights into the suitability of earthworms as potential candidates for bioremediation of PTEs contaminated soils and mitigating environmental and human health risks. Specifically, we reviewed and discussed: i) the occurrence and abundance of earthworms in PTEs contaminated soils; ii) the influence of PTEs on earthworm communities in contaminated soils; iii) factors affecting earthworm PTEs accumulation and elimination, and iv) the dynamics and fate of PTEs in earthworm amended soils. The technical feasibility, knowledge gaps, and practical challenges have been worked out and critically discussed. Therefore, this review could provide a reference and guidance for bio-restoration of PTEs contaminated soils and shall also help developing innovative and applicable solutions for controlling PTEs bioavailability for the remediation of contaminated soils and the mitigation of the environment and human risks.